The operative management in Bariatric Acute Abdomen (OBA) survey: Long-term complications of bariatric surgery and the emergency surgeon's point of view - De Simone B.; Ansaloni L.; Sartelli M.; Kluger Y.; Abu-Zidan F.M.; Biffl W.L.; Heyer A.; Coccolini F.; Baiocchi G.L.; Campanile F.C.; Mario D.; Kim D.; et al. (BioMed Central Ltd., 2024)
Indexed by WOS/ Scopus